The Role Of Nahdlatul Ulama On Indonesian National Movement On 1926 - 1945 - Anisatul Khoir Aprilia; Sugiyanto Sugiyanto; Sri Handayani (JURNAL HISTORICA, 2017)
In 1900â€™s there were counterwork movements which cause social restlessness in any area, and also the resurrection movement of religion which took a form of schools such as â€œmadrasahâ€ and organization in Indonesia. Moslemâ€™s figures are like Ulama and Kyai were starting to collect power through Pondok Pesantren and established a religious social organization, for example, Nahdlatul Ulama in Jombang (East Java) in 1926. The problems in this research is how did the background of NU takes a role in national movement and how was the pattern of NUâ€™s act on national movement from 1926-1945. This research aims to describe and analyze the background of NU on national movement and pattern of NUâ€™s act fom 1926-1945. This research uses historical research method. Source of data which was gotten in the first step is from primary and secondary source. Next, in the second step, the researcher gave sourceâ€™s critic which are external and internal critic. The third step is an interpretation which was done using analysis and synthesis. The final step, the researcher used historiography or presentation of the result of factâ€™s interpretation in written form. The result of research covers some things. First, the backgrounds or the reasons NU took part on Indonesian national movement which was affected by politics condition, social, economy and education during the Dutch and Japanese colonization. The second, the pattern of NU movement during the Dutch and Japanese colonization had been implemented. In the Dutch colonization, NU refused the idea which proposed its members be in Volksraad. Meanwhile, during Japanese colonization, NU decided to be more cooperative by using collaboration issue or be cooperative with Japanese government.